2011
DOI: 10.1371/journal.pone.0018991
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Plant bos1 Mutant Highlights Necrosis as an Efficient Defence Mechanism during D. dadantii/Arabidospis thaliana Interaction

Abstract: Dickeya dadantii is a broad host range phytopathogenic bacterium provoking soft rot disease on many plants including Arabidopsis. We showed that, after D. dadantii infection, the expression of the Arabidopsis BOS1 gene was specifically induced by the production of the bacterial PelB/C pectinases able to degrade pectin. This prompted us to analyze the interaction between the bos1 mutant and D. dadantii. The phenotype of the infected bos1 mutant is complex. Indeed, maceration symptoms occurred more rapidly in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…Surprisingly, our pathogenicity assays clearly showed that NAD-induced defense is effective against a range of pathogens with different lifestyles (Fig. 1), including the avirulent hemibiotrophic pathogen Pst-AvrRpt2 and the virulent hemibiotrophic pathogen D. dadantii (which are resisted by SA-and ROSrelated defenses; Katagiri et al, 2002;Fagard et al, 2007;Kraepiel et al, 2011) as well as the necrotrophic pathogen B. cinerea (which is sensitive to JA-dependent defenses; Glazebrook, 2005). Our metabolomics analysis has demonstrated that exogenously applied NAD and intracellular accumulation of NAD simultaneously increased pools of SA, JA, and ABA (Table I; Supplemental Fig.…”
Section: Nad-mediated Defense Is Effective Against Pathogens With DIVmentioning
confidence: 93%
“…Surprisingly, our pathogenicity assays clearly showed that NAD-induced defense is effective against a range of pathogens with different lifestyles (Fig. 1), including the avirulent hemibiotrophic pathogen Pst-AvrRpt2 and the virulent hemibiotrophic pathogen D. dadantii (which are resisted by SA-and ROSrelated defenses; Katagiri et al, 2002;Fagard et al, 2007;Kraepiel et al, 2011) as well as the necrotrophic pathogen B. cinerea (which is sensitive to JA-dependent defenses; Glazebrook, 2005). Our metabolomics analysis has demonstrated that exogenously applied NAD and intracellular accumulation of NAD simultaneously increased pools of SA, JA, and ABA (Table I; Supplemental Fig.…”
Section: Nad-mediated Defense Is Effective Against Pathogens With DIVmentioning
confidence: 93%
“…8). Several studies demonstrated that resistance against B. cinerea (and other necrotrophs) is accompanied by the generation of ROS, and mutants impaired in ROS production failed to resist the necrotrophic pathogen (Contreras-Cornejo et al, 2011;Kraepiel et al, 2011;L'Haridon et al, 2011;Rasul et al, 2012;Savatin et al, 2014;Zhang et al, 2014). It has been shown that LCBs but not LCB-Ps alone are able to induce ROS production (Peer et al, 2011).…”
Section: Interconnections Between Sphingolipids and Defense Mechanismsmentioning
confidence: 99%
“…Aerial plant tissues were collected at different time points post-inoculation and ground in liquid nitrogen to a fine powder. This infection procedure, close to a natural leaf infection by splashing, was compatible with short studies of infection rate and avoided wound-related transcriptional responses (Kraepiel et al, 2011). …”
Section: Methodsmentioning
confidence: 79%
“…Dickeya dadantii strains used in this study derived from the 3937 wild type (WT) strain and were previously described (Kraepiel et al, 2011). The secretion mutants prtE , outC , and hrcC are respectively impaired in the type I, type II, and type III protein secretion systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation